Perilaku Seks Bebas Remaja: Tantangan Formasi Iman Kaum Muda Gereja Indonesia - Agustinus Abraham (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study examines the increasing prevalence of premarital sexual behavior among Indonesian adolescents, including Catholic youths, which poses a significant challenge to the moral formation and faith development promoted by the Catholic Church. Using a qualitative method with a literature study approach, this research analyzes the phenomenon of adolescent free sex from the perspective of Catholic moral theology and family pastoral care. The findings reveal that the rise of free sexual behavior among adolescents is strongly influenced by curiosity, fragmented family structures, weak value-based sexual education, and the unregulated use of digital media. Moral theology views sexuality as a divine gift whose authentic meaning is realized only within the sacramental bond of marriage; therefore, premarital sex is considered a deviation from human dignity and the true nature of love. The study also highlights the essential role of the family as the Domestic Church in shaping conscience, character, and responsible sexual attitudes among youths. Pastoral strategies proposed include integral sexual education, strengthening parent–child communication in the digital age, and contextual pastoral accompaniment rooted in compassion, as emphasized in Amoris Laetitia. This research underscores the need for collaborative efforts between families, the Church, and educational institutions to guide young people toward a holistic understanding of sexuality, authentic love, and their Christian vocation in contemporary society.